(3QSGdI ajeG JbQQ aj MLL GdeKHJjf ddeGVi eHOGkA ReGfjkG hJMdjdgG Edi GdbjGSGJs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd GdTjN CHh Ydi GdMSjf Hf YHO Gddg Hf SjfG gPg QSGdI YedJgG ajeG JbQQ YfOi ef GdMcheI ai EKHGJ MLL GdeKHJjf s
(3BNQgG (B:s
(3adfNJe GdebGdg JeJ GdebGdI HMeO Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi (B(7473) s
Keywords: (3GdJhMjO hGdedd hGdfMds